2019
DOI: 10.1210/jc.2019-00129
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Improves Peripheral Insulin Sensitivity in Youth With Type 1 Diabetes

Abstract: Context Type 1 diabetes in adolescence is characterized by insulin deficiency and insulin resistance (IR), both thought to increase cardiovascular disease risk. We previously demonstrated that adolescents with type 1 diabetes have adipose, hepatic, and muscle IR, and that metformin lowers daily insulin dose, suggesting improved IR. However, whether metformin improves IR in muscle, hepatic, or adipose tissues in type 1 diabetes was unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 46 publications
0
103
0
Order By: Relevance
“…1). There is clear evidence of elevated left ventricular mass, abnormal cardiac geometry and impaired diastolic function, reduced cardiopulmonary fitness, abnormal limb blood flow, arterial stiffness and higher blood pressure, as well as renal hyperfiltration, in both diabetes types compared with peers without diabetes with a similar BMI [24,[48][49][50][51][52][53][54][55][56][57][58][59]. However, some comorbidities including low HDL-cholesterol and elevated triacylglycerol, hepatic fat [54] and liver transaminases [60], and non-alcoholic steatohepatitis (NASH) [61] are not typically present in youth with type 1 diabetes, especially in those with a normal BMI.…”
Section: Comorbidities and Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). There is clear evidence of elevated left ventricular mass, abnormal cardiac geometry and impaired diastolic function, reduced cardiopulmonary fitness, abnormal limb blood flow, arterial stiffness and higher blood pressure, as well as renal hyperfiltration, in both diabetes types compared with peers without diabetes with a similar BMI [24,[48][49][50][51][52][53][54][55][56][57][58][59]. However, some comorbidities including low HDL-cholesterol and elevated triacylglycerol, hepatic fat [54] and liver transaminases [60], and non-alcoholic steatohepatitis (NASH) [61] are not typically present in youth with type 1 diabetes, especially in those with a normal BMI.…”
Section: Comorbidities and Complicationsmentioning
confidence: 99%
“…A recent meta-analysis of 13 randomised controlled metformin trials in type 1 diabetes found significant improvements in BMI and reductions in insulin requirements, total cholesterol and LDL-cholesterol [77], but little or no decrease in HbA 1c . Short-term paediatric data suggest similar metabolic improvements in youth [78,79], along with improvements in insulin sensitivity [53] and vascular health on imaging [79], but data on long-term benefits of metformin in type 1 diabetes are currently lacking.…”
Section: Treatmentmentioning
confidence: 99%
“…2. Lower daily insulin dose improved whole-body and peripheral insulin resistance in adolescents with T1D who were overweight/obese [76]. 3.…”
Section: Pediatric T1dmentioning
confidence: 99%
“…Improvement in HbA1c level in adolescents with T1D [79,80]. In contrast, some trials did not observe improvement in HbA1c [76,81], or glycemic control. As expected, there was an increased gastrointestinal adverse event in overweight adolescents with T1D [81].…”
Section: Pediatric T1dmentioning
confidence: 99%
“…Given increasing support for the role of specific diets in the promotion of a pro-inflammatory state that is associated with T1DM (Vaarala 2011, Knip et al 2012, van Bussel et al 2013 and ENDO (Saguyod et al 2018, it is prudent to consider dietary changes, which can significantly impact the intestinal microbiota, for management of co-morbid ENDO and T1DM (Henschel et al 2018). Similarly, the use of metformin for targeting co-morbid T1DM and ENDO may have value, given recent evidence for its efficacy in reducing T1DM (Bjornstad et al 2018, Cree-Green et al 2019 and hindering the progression of ENDO lesions and associated signaling pathways (Takemura et al 2007, Yilmaz et al 2010. Additionally, therapies that reduce inflammation could prove beneficial, given the pro-inflammatory status of T1DM and ENDO.…”
Section: Potential Therapeutic Complications In Co-morbid T1dm and Endomentioning
confidence: 99%